Human articular chondrocytes express functional leukotriene B(4) receptors - Hansen, Ann Kristin (J Anat, 2015)
Leukotriene B(4) (LTB(4)) is a potent chemoattractant associated with the development of osteoarthritis (OA), while its receptors BLT1 and BLT2 have been found in synovium and subchondral bone. In this study, we have investigated whether these receptors are also expressed by human cartilage cells and their potential effects on cartilage cells. The expression of LTB(4) receptors in native tissue and cultured cells was assessed by immunohistochemistry, immunocytochemistry, polymerase chain reaction (PCR) and electron microscopy. The functional significance of the LTB(4) receptor expression was studied by Western blotting, using phospho-specific antibodies in the presence or absence of receptor antagonists. In further studies, the secretion of pro-inflammatory cytokines, growth factors and metalloproteinases by LTB(4)-stimulated chondrocytes was measured by multiplex protein assays. The effects of LTB(4) in cartilage signature gene expression in cultured cells were assessed by quantitative PCR, whereas the LTB(4)-promoted matrix synthesis was determined using 3D pellet cultures. Both receptors were present in cultured chondrocytes, as was confirmed by immunolabelling and PCR. The relative quantification by PCR demonstrated a higher expression of the receptors in cells from healthy joints compared with OA cases. The stimulation of cultured chondrocytes with LTB(4) resulted in a phosphorylation of downstream transcription factor Erk 1/2, which was reduced after blocking BLT1 signalling. No alteration in the secretion of cytokine and metalloproteinases was recorded after challenging cultured cells with LTB(4); likewise, cartilage matrix gene expression and 3D tissue synthesis were unaffected. Chondrocytes express BLT1 and BLT2 receptors, and LTB(4) activates the downstream Erk 1/2 pathway by engaging the high-affinity receptor BLT1. However, any putative role in cartilage biology could not be revealed, and remains to be clarified.